Ocupação e mortalidade na Marinha do Brasil Occupation and mortality in the Brazilian Navy - Marlene Silva; Vilma Sousa Santana (Universidade de São Paulo, 2004)
OBJETIVO: Descrever a distribuição da mortalidade por doenças do aparelho digestivo, geniturinário e do sistema nervoso, de acordo com a ocupação entre militares da Marinha do Brasil. MÉTODOS: Estudo exploratório da mortalidade proporcional conduzido com militares do sexo masculino lotados na Marinha do Brasil, que faleceram no período de 1991 a 1995. A população do estudo corresponde a todo o contingente da corporação nesse mesmo período. Os dados provêm de certidões de óbitos requeridas para concessão de pensões de dependentes e história ocupacional correspondente. As causas básicas de morte foram codificadas de acordo a Classificação Internacional de Doenças (9ª revisão). RESULTADOS: Militares apresentaram mortalidade proporcional aumentada para as doenças do fígado relacionadas com o consumo do álcool (razão de mortalidade proporcional ajustada (RMPaj=2,03; IC 95%: 1,26 3,00), pancreatite (RMPaj=2,03; IC 95%: 1,06 3,38), hemorragia digestiva (RMPaj=1,61; IC 95%: 1,10 2,23), doenças renais crônicas (RMPaj=2,82; IC 95%: 1,98 3,84), doença de Parkinson (RMPaj=3,00; IC 95%: 1,27 5,72) e degenerações cerebrais (RMPaj=2,88; IC 95%: 1,14 5,70) em relação a população de referência. Associação não estatisticamente significante foi observada entre operadores de radar (RMP=6,50; IC 95%: 1,43 29,56) e doenças do sistema nervoso. CONCLUSÕES: Os resultados indicam a existência de possíveis fatores de riscos ocupacionais no ambiente de trabalho da Marinha do Brasil, e a necessidade de estudos com medidas quantitativas de exposição. OBJECTIVE: To describe the distribution of mortality due to digestive tract, genitourinary and nervous system diseases according to occupation among Brazilian Navy servicemen. METHODS: This was an exploratory study of proportional mortality among male servicemen in the Brazilian Navy who died between 1991 and 1995. The study population comprises the entire contingent of servicemen during this same time period. Data were obtained from death certificates submitted in order to obtain dependents' pensions, and from the corresponding occupational histories of these individuals. Basic causes of death were coded in accordance with the International Classification of Diseases (9th Revision). RESULTS: Servicemen presented increased proportional mortality for liver diseases related to alcohol consumption (age-adjusted proportional mortality ratio, PMRadj =2.03; 95% confidence interval, CI: 1.26-3.00), pancreatitis (PMRadj=2.03; 95% CI: 1.06-3.38), digestive hemorrhage (PMRadj=1.61; 95% CI: 1.10-2.23), chronic kidney diseases (PMRadj=2.82; 95% CI: 1.98-3.84), Parkinson's disease (PMRadj=3.00; 95% CI: 1.27-5.72) and degenerative brain diseases (PMRadj=2.88; 95% CI: 1.14-5.70), in relation to the reference population. A statistically non-significant association was observed between radar operators (PMR=6.50; 95% CI: 1.43-29.56) and nervous system diseases was observed. CONCLUSIONS: The results indicate the existence of possible occupational risk factors in the working environment of the Brazilian Navy, and the need for studies using quantitative measurement of such exposure.